Peningkatan aktivitas dan hasil belajar IPS siswa dengan menggunakan media pembelajaran “Jendela Hidrosfer” - Martina Lona Jusita (Universitas Negeri Malang, 2017)
Hydrosphere material related to the hydrological cycle, forms the body of water, and marine zones according to depth as a material object IPS too elusive if only rely on the transfer of knowledge from the teacher to the learner; better if the students can see what is observed, which is then written and finally presented based learning experiences. Thus we need a media as an intermediary to help the learning process. To that end, the appropriate learning media is to use the “Jendela Hidrosfer”. Medium of learning not just as a mere intermediary; but can increase the activity and learning outcomes of students.Keywords: Learning activities, Learning outcomes, Instructional media “Jendela Hidorsfer” http://dx.doi.org/10.17977/um022v2i12017p037